REAKSI PASAR TERHADAP PENGUMUMAN DIVIDEN PADA PERUSAHAAN YANG MASUK CORPORATE GOVERNANCE PERCEPTION INDEX - EVI GANTYOWATI; YAYUK SULISTIYANI (Jurnal Bisnis dan Akuntansi, 2008)
The objective of this research is to empirically examine about the market reaction to dividend announcement at the firms included Corporate Governance Perception Index (CGPI). The analysis includes two aspects: Security Return Variability (SRV) and Trading Volume Activity (TVA) of dividend announcement. The sample of this research is the firms that included Corporate Governance Perception Index (CGPI) at the period of 2003–2005 and they have dividend announcement at the period of 2004–2006. Based on purposive sampling method, the sample used in this research is 58 firms. Data were analyzed using one sample t-test. The results of this research show that dividend announcement at the firms included Corporate Governance Perception Index (CGPI) has information content and statistically significant responded by the market around the date dividend announcement.